Body image and dieting behaviors among elite figure skaters - Ziegler, P. J.; Khoo, C. S.; Sherr, B.; Nelson, J. A.; Larson, W. M.; Drewnowski, A. (International Journal of Eating Disorders, 1999)
OBJECTIVE: This study explored links among body image, dieting behavior, and nutritional status among 40 nationally ranked junior figure skaters. METHOD: Questionnaires were provided to 40 junior skaters (range 12.9-22.9 years) during a skaters' camp. Food intakes were recorded over 4 consecutive days and blood samples were drawn. Nutritional status was assessed using food intake records and selected biomarker data. RESULTS: Data suggested that these athletes dieted despite relative satisfaction with body image. Although biochemical measures of nutritional status were all within normal range, inadequate energy intakes and delayed menarche (in women) were widespread in this athlete sample. DISCUSSION: Data dispute common theories of dieting being linked to dissatisfaction with body image. The article also cautions against overreliance on biochemical assessment as a marker of nutritional inadequacy.